2016
DOI: 10.1080/15476286.2016.1256533
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Pr55Gagbinds genomic and spliced RNAs with different affinity and stoichiometry

Abstract: The HIV-1 Pr55 precursor specifically selects genomic RNA (gRNA) from a large variety of cellular and spliced viral RNAs (svRNAs), however the molecular mechanisms of this selective recognition remains poorly understood. To gain better understanding of this process, we analyzed the interactions between Pr55 and a large panel of viral RNA (vRNA) fragments encompassing the main packaging signal (Psi) and its flanking regions by fluorescence spectroscopy. We showed that the gRNA harbors a high affinity binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 115 publications
(186 reference statements)
11
79
0
Order By: Relevance
“…This is fully consistent with the notion that Gag multimerization could be initiated in the cytoplasm, and then triggered by RNA binding, (26,75,76,(87)(88)(89), and with our previous in vitro data showing that a limited number of Gag proteins (i.e. about two trimers) bind to gRNA fragments (14). Deletion of the NC domain induced a significant increase in diffusion compared to WT Gag (4.7 ± 1 µm²/s vs 1.1 ± 0.6 µm²/s), in line with previous data on Gag mutants in which all basic residues of the NC domain were replaced by Ala residues (77).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is fully consistent with the notion that Gag multimerization could be initiated in the cytoplasm, and then triggered by RNA binding, (26,75,76,(87)(88)(89), and with our previous in vitro data showing that a limited number of Gag proteins (i.e. about two trimers) bind to gRNA fragments (14). Deletion of the NC domain induced a significant increase in diffusion compared to WT Gag (4.7 ± 1 µm²/s vs 1.1 ± 0.6 µm²/s), in line with previous data on Gag mutants in which all basic residues of the NC domain were replaced by Ala residues (77).…”
Section: Discussionsupporting
confidence: 92%
“…This process involves specific interactions between Gag and the 5' end of the gRNA which contains the packaging signal (Psi) encompassing stem-loop 1 (SL1) to SL4 ( Figure 1A) (for reviews see (4)(5)(6)(7)). SL1 corresponds to the Dimerization Initiation Site (DIS), as it contains a short palindromic sequence in its apical loop that drives dimerization of the HIV-1 gRNA (8)(9)(10)(11)(12), and our group previously showed that the SL1 internal purine rich loop corresponds to a major Gag recognition signal (13)(14)(15). SL2 contains the major splice donor site, SL3 has been historically considered as the main packaging signal (16,17), and SL4 contains the translation initiation codon of Gag.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently SL3, which is present downstream of mSD, had been proposed to be the main HIV-1 packaging signal since it harbors a conserved region containing a GGAG tetraloop that has been shown to bind NC [43]. However, it has now been shown that SL1, in addition to containing the HIV-1 DIS, also harbors a single-stranded purine rich internal loop (ssPurine: GAGG) that acts as the main site for HIV-1 Gag binding during gRNA packaging [26,30,44,45]. This internal ssPurine loop as well as the DIS, however, are located upstream of the mSD and therefore are part of both the spliced and unspliced viral mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This internal ssPurine loop as well as the DIS, however, are located upstream of the mSD and therefore are part of both the spliced and unspliced viral mRNA. Thus, in the case of HIV-1, selection of the gRNA for packaging is likely to be dependent upon the higher order structure of the major packaging determinant of the gRNA which is disrupted upon splicing [26,30,44,45]. In the case of HIV-2, even though both the spliced and unspliced viral mRNAs harbor RNA packaging sequences, only the unspliced message is packaged into nascently formed virus particle since HIV-2 Gag preferentially package gRNA in cis [46–48].…”
Section: Discussionmentioning
confidence: 99%
“…Psi is composed of three stemloops (SL1, SL2, SL3) with a conserved GC-rich palindromic dimerization initiation site (DIS) located within SL1. Although dimerization of gRNA appears to be required for its packaging in vivo (12,33), whether specific interaction of Gag with Psi depends on dimerization in vitro is less clear (7,9,10,16,(34)(35)(36). Because Gag can assemble around non-gRNA in the cell, we hypothesize that Gag-Gag interactions are facilitated by NC domain binding to Psi in a manner that is distinct from binding to non-Psi RNA sequences.…”
Section: Introductionmentioning
confidence: 94%